Theory of probing attosecond electron wave packets via two-path interference of angle-resolved photoelectrons - Choi, N. N.; Jiang, T. F.; Morishita, T.; Lee, M.-H.; Lin, C. D. (My University, 2010)
We study theoretically the electron wave packet generated by an attosecond pulse train (APT) which is probed with a time-delayed infrared (IR) laser pulse. The APT creates an excited state and a continuum electron wave packet. By ionizing the excited state with an IR, a delayed new continuum electron wave packet is created. The interference of the wave packets from the two paths, as reflected in angle-resolved photoelectron spectra, is analyzed analytically. Using the analytical expressions, we examine the possibility of retrieving information on the electron wave packet generated by the APT.